Effects of Maternal Storytelling-Based Stimulation on Language Development among Preschool Children: A Quasi-Experimental Study - Sinaga, Desriati; S, R. Oktaviance.; Bangun, Seri Rayani; Tarigan, Rica Vera Br; Derang, Imelda; EL-Matury , Herlina J. (Journal of Applied Nursing and Health, 2026)
Background: The age of 3–4 years is a critical period for children’s language development, strongly influenced by environmental stimulation, particularly from mothers as primary caregivers. Storytelling is a simple and practical method for language stimulation, yet quantitative evidence of its effectiveness in community or family settings remains limited. Therefore, this study aimed to analyze the effect of maternal storytelling stimulation on the language development of children aged 3–4 years. Methods: This study employed a quasi-experimental design using a one-group pretest–posttest approach. A total of 44 mother–child pairs with children aged 3–4 years were selected through purposive sampling. Participants received education and structured guidance to implement storytelling-based language stimulation over four weeks. Children’s language development was assessed using a language screening instrument adapted from the KPSP. As the data were not normally distributed, the Wilcoxon signed-rank test was used for analysis with a significance level of 0.05. Results: The findings demonstrated a statistically significant increase in children’s language development scores following the intervention. Conclusion: Maternal stimulation using the storytelling method significantly improves language development in children aged 3–4 years. This approach is recommended as an evidence-based language stimulation strategy at the family and community levels